Using the A* algorithm to build DNA nanostructures - Hedbrandh, Christofer (My University, 2010)
In this project a suggested idea for an abstraction of simplex DNA was used to simulate DNA behavior. Furthermore, the A* search algorithm was used to construct a sequence of simplex DNA strands used to build a desired DNA structure. DNA nanotechnology is a subfield of nanotechnology where DNA is used as structural material. DNA origami is an example of an accomplishment in this field, where short "staple" strands are used to fold up a longer DNA stand in order to produce 2 dimensional shapes. Demonstrated designs have included a smiley face and a map of the Americas. Various different DNA "machines" such as DNA tweezers, which can operate with nanoscale precision, and DNA walkers, which can walk along a track of DNA, have been built. Potential applications for these machines are within nanorobotics and nanomedicine. The abstraction of simplex DNA consists of reducing sequences of DNA bases to single entities, and of discarding some odd and unusual behavior. This simplification makes it feasible to perform quick simulations, and still deliver simulated results comparable to the actual.
Keywords: Datalogi; Bioinformatik och systembiologi; Computer science; Bioinformatics and Systems Biology